2015
DOI: 10.1016/j.shaw.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Does Leaders' Health (and Work-Related Experiences) Affect their Evaluation of Followers' Stress?

Abstract: BackgroundStressed workers suffer from severe health problems which appear to have increased. Poor leadership is especially considered a source of stress. Indeed, supervisors might perceive their subordinates to be similar to them as far as stress is concerned and this might more widespread in organizations than previously thought.MethodsThe present research investigates the relationships between leaders' health, in terms of work-related stress, mental health, and workplace bullying and their evaluation of sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Consequently, these results suggest a series of guidelines for HR managers, who should develop specific training plans and seek to appreciate every single learning outcome, with relentless attention paid to the wellbeing and stress of their employees: in line with other scholars (Montani et al, 2015; Giorgi et al, 2015) we claim for a supervisors’ empowering management practices…”
Section: Discussionsupporting
confidence: 74%
“…Consequently, these results suggest a series of guidelines for HR managers, who should develop specific training plans and seek to appreciate every single learning outcome, with relentless attention paid to the wellbeing and stress of their employees: in line with other scholars (Montani et al, 2015; Giorgi et al, 2015) we claim for a supervisors’ empowering management practices…”
Section: Discussionsupporting
confidence: 74%
“…If we are to assume that employees use CWBs to compensate for increased demands or stressors, research focusing on daily recovery or general indicators of wellbeing, can determine whether this strategy is effective. Finally, as leaders appear to reflect their own feelings of stress to subordinates ( Giorgi et al, 2015b ), it is interesting to research this dyadic relationship, and examine whether the leaders’ perceived pressure to engage in citizenship behaviors spills over to their subordinates.…”
Section: Discussionmentioning
confidence: 99%
“…However, leaders were more likely to be abusive when they felt that followers performed poorly, and followers tended to be less distressed if they possessed higher levels of psychological capital (Li, Wang, Yang, & Liu, 2016). Exploring leaders' perceptions, Giorgi, Mancuso, Perez, Montani, Courcy, and Arcangeli (2015) found that leaders who were stressed also perceived their followers to suffer from stress. We need to develop our understanding of the complex crossover from leaders to their followers.…”
Section: Leading Well: 11mentioning
confidence: 99%